Research output in the department of sociology in Iraq: Analytical-statistical study of what was produced in postgraduate studies - hantoosh sachit, khalid (Al-Adab Journal, 2019)
Since the establishment of graduate studies in the department of sociology of mother by the first generation of professors of the department in 1972 and so far no one dared to do an analytical study - a calendar of what was done during this period, which reached 48 years and the existence of 608 master and doctoral thesis, so the researcher tries In this research, a quantitative analytical vision is produced as a result of the beginning of the title page. It continues in the other parts of the study in subsequent research and is based on the statistical method, with a basic objective to review what was produced and using simple statistical indicators to complete this analysis. This period is used C (19) a table in his analytical title page during which he discovered many of the problems and reached many of the results Perhaps the most important: - 1-There is an annual increase in the number of letters and permits that vary according to the years and by (53.29%) every ten years. The question that arises here is whether there is an increase or improvement in the quality of what is written each year corresponding even relatively quantitative increase. 2-There is a disparity in the ratio of admission to postgraduate studies in the section tends to favor males. This gender disparity persists throughout the last 46 years of life in Milan in favor of males, with no mention of gender discrimination against females in the admission system. 3 - Field studies in the department have a predominance of analytical studies in graduate research in the department with a difference in the proportion of analytical studies between the master’s and doctorate degrees are leaning towards the doctorate. 4 - The topics of graduate studies in the department vary in their specialization focus on topics and neglect of other subjects, which reveals the lack of a clear plan / vision for the development of sociology in Iraq. 5 - The ideal number of the words of thesis or letter is approximately (9) words and the reality of the middle of the account (8.7) and standard deviation (3.208) Note the mathematical mean of the number of words of the letters is (8.51) words and master letters is (8.81) word. There is an uneven geographical distribution of the field study sites in the department because there is a focus on the city of Baghdad and neglect of other areas of Iraq, which reveals the lack of plans to study Iraq socially. The researcher made many recommendations and suggestions and provided at the end of the research a list of all the titles of messages and papers for the benefit of